An Empirical Study on Market Timing Theory of Capital Structure - Setyawan, Ignatius Rony (International Research Journal of Business Studies, 2011)
The theory of capital structure has advanced remarkably. Thisdevelopment began as many firms had options to consider various external factors determining the composition of debt and equity. Not only the asymmetric information or the conflict among bondholders and shareholders initiated the Pecking Order Theory and the Static Trade-off Theory respectively but also the overvalued or undervalued of stock price had to be taken as a determinant factor for identifying the ideal debt-equity mix. The author maintains these factors as they were pioneers to this theory on Market Timing Theory (MTT) introduced by Baker and Wurgler (2002). The essence of this theory is described when stock prices are overvalued, firms will finance projects through debts, otherwise the firms will be undervalued and be relied on equity financing. Using the methodology introduced by Baker and Wurgler (2002), the author selected only samples of IPOs of firms during 2008-2009 to limit the scope of this study. The main objective of this study is to test the hypothèses of Market Timing Theory formulated by Dahlan (2004) and by Kusumawati and Danny (2006) which have been proven by the GLS model, and the OLS model-like as in Baker and Wurgler (2002), Susilawati (2008) and Saad (2010). This study concludes that the market-to-book ratio has a negative effect on the market leverage. The implication is that when firms achieve certain level of earnings growth, the stock price will be overvalued, so it would be the right timing for firms to proceed equity financing. Under the robustness test with GLS Random Effect, the hypothèses of MTT is supported.